PENGUATAN KETERAMPILAN KOMUNIKASI INTERPERSONAL DALAM MEWUJUDKAN LINGKUNGAN SEKOLAH BEBAS BULLYING - Syahrul Hidayanto; Wa Ode Sitti Nurhaliza; Siti Zulfah; Fajar Ramadhan (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2026)
Bullying in school environments has shown a significant increasing trend, particularly at the secondary education level. Bullying, especially in its verbal form, not only affects students’ psychological well-being but also influences the quality of interpersonal communication and social relationships within schools. This issue requires preventive efforts that are not merely regulatory, but also educational and participatory in nature. This Community Service program aimed to strengthen students’ interpersonal communication skills as a strategy to prevent bullying and to promote a safe and bullying-free school environment. The activity was conducted at Madrasah Aliyah Negeri (MAN) 1 Bekasi and involved senior high school students as participants. A participatory-educational approach was employed through interactive lectures, group discussions, and educational games. The results indicate an improvement in students’ understanding of bullying concepts and forms, particularly verbal bullying, which had previously been perceived as harmless joking. Furthermore, students demonstrated increased awareness of the importance of healthy interpersonal communication skills, such as empathy, assertive communication, and active listening, in building positive social relationships. Experiential learning through educational games enabled students to reflect on the emotional impacts of bullying and the significance of adopting respectful communication practices. This community service activity demonstrates that strengthening interpersonal communication skills can serve as an effective strategy for bullying prevention in school settings. Through this program, communication studies contribute practically to fostering positive communication cultures and supporting the creation of a more humane and equitable educational environment.